2018
DOI: 10.3127/ajis.v22i0.1680
|View full text |Cite
|
Sign up to set email alerts
|

Standard Business Reporting (SBR) Adoption in Australia, Critically Acclaimed, Box Office Flop: Constructivist and Ecological Rationalities in Information Systems (IS) Adoption

Abstract: IS enables organizations to improve their productivity, streamline their business processes, and better understand the challenges and opportunities facing their business. These benefits can further accrue to individuals and organizations when they adopt and use the systems. While the benefits of IS are multifarious, IS adoption remains challenging. The far-reaching consequences of IS motivate research examining the antecedents of successful IS adoption both at individual and organizational levels. To examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, this would be a challenge for XBRL adoption if there is a lack of tools and software in the market (Troshani & Doolin, 2005;Troshani & Rao, 2007;David, 2016). Not surprisingly happened in Australia when Perdana et al (2018) when there is a lack of companies that provide accounting software that embedded with XBRL taxonomy for filers particularly for small companies. But in Malaysia, we have problems for small and medium-sized companies.…”
Section: Officer C2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this would be a challenge for XBRL adoption if there is a lack of tools and software in the market (Troshani & Doolin, 2005;Troshani & Rao, 2007;David, 2016). Not surprisingly happened in Australia when Perdana et al (2018) when there is a lack of companies that provide accounting software that embedded with XBRL taxonomy for filers particularly for small companies. But in Malaysia, we have problems for small and medium-sized companies.…”
Section: Officer C2mentioning
confidence: 99%
“…Since Malaysia is still new in the field of XBRL development, there is a lack of tools and software for filers, which could pose a challenge for XBRL adoption. With this lack of tools and software, there is a need to regulator to ensure the availability of appropriate tools and software in the market to facilitate the adoption of XBRL (Perdana et al, 2018).…”
Section: Officer C2mentioning
confidence: 99%
“…Compare with Alkhatib, Ojala, and Collis (2019) in UK scenario has found the high cost of preparation of XBRL submission among filers from small companies that use commercial filing software and consequently consider the software and set-up costs of digital reporting. While in Australia, Perdana, Robb, Rohde, and Birt (2018) has suggested that the cost of regulatory and business reporting will reduce due to the XBRL submission. Thus, this can indicate that the cost of preparation and submission by filers has shown differently among different countries and method of XBRL submission.…”
Section: Decision Making Phasementioning
confidence: 99%